Enhancing the carbonation of MgO cement porous blocks through improved curing conditions - Unluer, C. (2014)
The use of reactive magnesia (MgO) as the binder in porous blocks demonstrated significant advantages due to its low production temperatures and ability to carbonate, leading to significant strengths. This paper investigates the enhancement of the carbonation process through different curing conditions: water to cement ratio (0.6–0.9), CO2 concentration (5–20%), curing duration (1–7 days), relative humidity (55–98%), and wet/dry cycling frequency (every 0–3 days), improving the carbonation potential through increased amounts of CO2 absorbed and enhanced mechanical performance. UCS results were supported with SEM, XRD, and HCl acid digestion analyses. The results show that CO2 concentrations as low as 5% can produce the required strengths after only 1 day. Drier mixes perform better in shorter curing durations, whereas larger w/c ratios are needed for continuous carbonation. Mixes subjected to 78% RH outperformed all the others, also highlighting the benefits of incorporating wet/dry cycling to induce carbonation.